Classification of spelt cultivars based on differences in storage protein compositions from wheat. (1st February 2015) - Koenig, Annette; Konitzer, Katharina; Wieser, Herbert; Koehler, Peter
Highlights: RP-HPLC patterns of protein fractions are suitable tools to distinguish common wheat and spelt wheat. The RP-HPLC chromatograms of the reduced gliadin fraction can be used to classify spelt cultivars. Glutenin-bound ω-gliadins are typical of wheat and could be used to detect common wheat in spelt wheat and products thereof. Abstract: Wholemeal flours from 62 spelt and 13 wheat cultivars were studied. The quantitative protein compositions of the Osborne fractions determined by reversed-phase high-performance liquid chromatography, showed that the chromatograms of the reduced gliadin fractions were most suitable for the distinction of spelt from wheat and for the classification of spelt. The patterns of the reduced spelt gliadins showed one to three markers that were not present in wheat. Based on these markers, spelt cultivars were classified into three groups ranging from 'typical spelt' to 'similar to common wheat'. Marker 1 was identified as ω1, 2-gliadin and markers 2, 3a and 3b were identified as γ-gliadins by means of N-terminal sequence analysis and determination of the relative molecular mass by mass spectrometry. As glutenin-bound ω-gliadins were present in wheat and absent in spelt, this protein type may be used to detect and quantitate small amounts of wheat in spelt products.